Design of the FINS-TEENS study: A randomized controlled trial assessing the impact of fatty fish on cognitive performance in adolescents. Issue 6 (August 2017) - Skotheim, Siv; Dahl, Lisbeth; Handeland, Katina; Frøyland, Livar; Lie, Øyvind; Øyen, Jannike; Kjellevold, Marian; Stormark, Kjell Morten; Graff, Ingvild Eide
Aims: To describe the rationale, study design, population and dietary compliance in a randomized controlled trial (RCT) investigating the effect of fatty fish on cognitive performance and mental health in adolescents. Method: In the Fish Intervention Studies-TEENS (FINS-TEENS) study we individually randomized 478 adolescents (14–15-year-olds) from eight secondary schools in Norway to receive school meal lunches with fatty fish or meat or n-3 supplements three times a week for 12 weeks. Demographic factors, psychological tests and biological measures were collected pre-and post-intervention. Duplicate portions of lunch meals were collected and individual intake recorded throughout the study. Results: In total, 481 out of 785 adolescents (61%) agreed to participate and 34 (7%) dropped out. Breakfast consumption was the only group difference in background characteristics. Analyses of selected nutrients in the lunch meals showed higher levels of n-3 fatty acids, vitamin D and n-6 fatty acids in the fish compared to the meat meals. Dietary compliance (score 0–144) revealed that the intake in the Fish group (mean = 59, standard deviation (SD) = 35) were lower than in the Meat group (mean = 83, SD = 31, p < 0.01) and Supplement group (mean = 105, SD = 25, p < 0.01). Conclusions: The results show that it is possible to conduct a RCT with fatty fish in a school-based setting. The results also emphasize the importance of collecting detailed records of dietary compliance, as this information is important when interpreting and analysing the outcome of dietary interventions.